The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s0100-204x2013000900012
|View full text |Cite
|
Sign up to set email alerts
|

Promoção do crescimento vegetal e diversidade genética de bactérias isoladas de nódulos de feijão-caupi

Abstract: Resumo -O objetivo deste trabalho foi avaliar o potencial de promoção do crescimento vegetal e a diversidade genética de bactérias isoladas de nódulos de feijão-caupi cultivado em solos do Cerrado piauiense. Avaliaram-se 26 estirpes quanto à capacidade de fixar nitrogênio em vida livre, solubilizar fosfatos inorgânicos, produzir ácido-3-indolacético (AIA) na ausência e na presença do aminoácido triptofano (100 mg L -1 ), produzir nódulos e promover o crescimento de feijão-caupi em vasos Leonard. Nenhuma estirp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 21 publications
1
9
0
6
Order By: Relevance
“…In Brazil, where cowpea is an introduced species, a higher diversity of bacteria associated to the nodules has been described (Martins et al, 1997; Leite et al, 2009). Bacterial strains assigned to the phylum Firmicutes (genera Bacillus and Paenibacillus ) were obtained from root nodules of cowpea plants cultivated in Brazilian semi-arid soils (Costa et al, 2013). Particularly for the Amazonian region, a number of strains classified as Pseudomonas, Enterobacter (Gammaproteobacteria), Bacillus , and Paenibacillus were isolated from cowpea nodules (Jaramillo et al, 2013; Oliveira-Longatti et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, where cowpea is an introduced species, a higher diversity of bacteria associated to the nodules has been described (Martins et al, 1997; Leite et al, 2009). Bacterial strains assigned to the phylum Firmicutes (genera Bacillus and Paenibacillus ) were obtained from root nodules of cowpea plants cultivated in Brazilian semi-arid soils (Costa et al, 2013). Particularly for the Amazonian region, a number of strains classified as Pseudomonas, Enterobacter (Gammaproteobacteria), Bacillus , and Paenibacillus were isolated from cowpea nodules (Jaramillo et al, 2013; Oliveira-Longatti et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This evidence also indicates that Chryseobacterium is an established member of the bacterial community in the BEF soils. Several studies already isolated other NRE from cowpea nodules belonging to Proteobacteria, Firmicutes, and Actinobacteria phyla (Guimarães et al, 2012; Costa et al, 2013; Jaramillo et al, 2013) using standard media for rhizobial isolation. Nevertheless, Bacteroidetes, such as Chryseobacterium , were not obtained up to now, probably because the great part of environmental isolates from this genus are not able to metabolize mannitol (Cho et al, 2010), the carbon source preferred by rhizobia.…”
Section: Discussionmentioning
confidence: 99%
“…A maioria das estirpes de BFNN, aprovadas para espécies florestais, adubo verde, forrageiras e para grãos, pertence a esse gênero, e muitas já são usadas com sucesso há décadas, sem a perda de suas propriedades simbióticas, como as de soja e de feijão-caupi. Para uso com feijão-caupi, têm sido relatadas novas estirpes eficientes de Bradyrhizobium (Guimarães et al, 2012;Costa et al, 2013;Jaramillo et al, 2013), o que pode ser extrapolado também para guandu.…”
Section: Introductionunclassified
“…Partial amplification parameters, primer sequences, cycle conditions, and sequencing protocol of the 16S rRNA gene were previously described by Costa et al (2013). The quality of the sequences was analysed with the BioNumerics 7.1 software (Applied Maths, Austin, TX, USA).…”
Section: Isolation and Phenotypic Characterization Of Strainsmentioning
confidence: 99%
“…Studies have demonstrated that strains of the Bacillus genus can coexist with Bradyrhizobium in nodules and can nodulate and biologically fix nitrogen (Li, Wang, Chen, & Chen, 2008;Costa et al, 2013). It has been demonstrated that bacteria belonging to the Arthrobacter and Klebsiella genera are found in the rhizosphere in association with roots, or live freely in the soil, and promote plant growth (Kloepper, Lifshitz, & Zablotowicz, 1989;Glick, 1995).…”
mentioning
confidence: 99%